Los decretos de urgencia durante el interregno parlamentario en el Perú. Un riesgo de concentración del poder por parte del Presidente de la República - Espinoza Flores, Rodrigo Alonso (2024)
In September 2019, Peruvian President Martín Vizcarra dissolved the Congress of the Republic and called for extraordinary legislative elections. During the ensuing parliamentary interregnum, which is the time between the dissolution of the Congress and the installation of the new one, the Executive branch assumed legislative functions through urgency decrees, arguing that the Constitution allowed for extraordinary legislative measures. However, some scholars argued that these decrees extended beyond economic and financial matters, representing an overreach of power. The research poses two hypotheses: that the urgency decrees exceeded the constitutional matters and that they lacked sufficient political control to prevent power concentration. To address two hypotheses, a qualitative analysis is conducted on the urgency decrees issued during the parliamentary interregnum, examining their content and compatibility with the current constitutional framework, as well as a review of the events surrounding these norms. The research is divided into five chapters that include a summary of the emergency decrees concept, the context in which they are issued, a section on the methodological design, the state of the art regarding emergency decrees during the interregnum, and a evaluation of the decrees issued in that period, ending with the respective conclusions.